Physiological, biochemical and molecular signaling basis of cold stress tolerance in plants - Roychowdhury, Rajib; Das, Soumya Prakash; Sarkar, Puja; Khan, Zeba; Kumar, Ajay; Sarker, Umakanta; Sajeevan, Radha Sivarajan (Frontiers in Plant Science, 2025)
Cold stress significantly hampers plant growth, development, and yield, posing a threat to global food security. This review consolidates our understanding of the physiological, biochemical, and molecular mechanisms that enable plants to tolerate cold stress. Plants employ many strategies to mitigate the negative effects of cold, including osmotic adjustments, boosting antioxidant defences, accumulating osmoprotectants, and regulating cold-responsive genes via transcription factors such as C-repeat binding proteins. The CBF expression-1 C-repeat binding factors cold-regulated (ICE1-CBF-COR) genetic signalling pathway is vital for acclimatisation to low temperatures and boosting cold resistance. Understanding these systems is essential for producing crops capable of thriving in cold environments through breeding and biotechnology. Enhancing crop resistance to cold stress can promote sustainable agriculture and bolster food security amid climate change. This review highlights key findings, methodological limitations, and areas needing further research to support the development of cold-tolerant crop varieties in the face of climate change.